DETERMINAN TINGKAT PENGUNGKAPAN LAPORAN KEUANGAN PEMERINTAH DAERAH (Studi Kasus pada LKPD Kabupaten/Kota di Provinsi Jawa Tengah Tahun Anggaran 2014-2016) - Ferina Intan Lutfia, 14.05.52.0256; Maryono, Maryono (Students Journal of Accounting and Banking, 2018)
This study aims to examine the effect of the realized of revenue, size of local government, number of units under regional (SKPD), the life of the local government, the size of the legislature,and the intergovernmental revenue on the level of disclosure LKPD Regency / City in Central Java province.The study population was District / City of Central Java Province during the years 2014-2016 that have been audited by the BPK. The sample used is 105 local government financial statements are all the population sampled.This research data analysis methods using the multiple linear regression analysis by SPSS 19.The results showed that realized of revenue, number of units under regional (SKPD), and the ratio of self-sufficiency have significant effect on the level of disclosure LKPD. While variable size of local government, the life of local governments, intergovernmental revenue, and a legislative measure does not affect the level of disclosure LKPD.Keywords        : Level of Disclosure LKPD, realized of revenue, number of units under regional (SKPD), Local Government Size, Ratio Independence, Local Government Age, size of the Legislature, and the Intergovernmental Revenue